Akibat Hukum Wanprestasi Debitur Dalam Transaksi Elektronik Melalui Fitur Paylater Pada Aplikasi Shopee - Sahuleka, Chrysilla Angelica; Haliwela, Nancy Silvana; Pariela, Marselo Valentino Giovani (Faculty of Law Universitas Pattimura, 2025)
The life of society in meeting daily needs has undergone changes due to advancements in technology and science. To realize this development, it is regulated based on Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 on Electronic Information and Transactions as well as Articles 1313, 1320, 1338, 1243 of the Civil Code as a legal umbrella for the dynamics of society in conducting transactions and economic activities. One of the developments in community life, particularly in trade to meet economic needs, is the introduction of the PayLater feature on the Shopee application. This application facilitates users in making online purchases. In its use, this feature certainly has terms and conditions that bind every consumer credit user. One of the users of consumer credit is an actor with the initial 'G' who engaged in the purchasing process through the PayLater feature. This actor purchased an item at a higher price, making it impossible for them to pay the bill after the due date. This issue has caused the PayLater facility users to default by not following the procedures set forth by Shopee PayLater. This action has resulted in losses that can be claimed by Shopee PayLater. The type of research used is normative legal research, which is conducted by examining the principles and concepts of law, as well as statutory regulations. The problem approach used is the legislative approach and the conceptual approach. The sources of legal materials are primary, secondary, and tertiary. The procedure for collecting legal materials used is library data. The procedures for processing and analyzing legal materials used are primary, secondary, and tertiary legal materials, which are analyzed in this research. The results of this study indicate that the legal consequences of defaulting actions taken by the debtor result in liability, specifically the debtor's accountability based on fault to the creditor to compensate for the losses suffered by Shopee PayLater. In resolving default cases between the debtor and Shopee PayLater, the resolution can be done through both non-litigation and litigation. Non-litigation will provide convenience for the debtor as it offers cost efficiency compared to litigation.